Seven original compositions for jazz combo - Siukola, Jennifer (Ball State University, 2016)
“Seven Original Compositions for Jazz Combo” is a project inspired by the compositional and improvisational work of seven famous jazz trumpeters. These diverse players include Tom Harrell, Roy Hargrove, Kenny Dorham, Chet Baker, Lee Morgan, Miles Davis, and Scott Wendholt. Each musician influenced my compositions in various ways; I imitated the harmonic language of Tom Harrell and Kenny Dorham in my compositions “Lighthouse Reverie” and “Bog Walking” respectively, and the lyricism of Chet Baker in “I Kissed You Goodbye.” Roy Hargrove’s approach to melody provided the main influence for my 18-bar tune “The Shaft House,” while Miles Davis’s treatment of the blues form influenced “The Dawn Approaches Like Tears.” The elements of harp bop found in Lee Morgan’s music inspired my piece “Lil’B Jr.,” and Scott Wendholt’s flowing, wavelike lines shaped the melody of “The Homp Romp.” The instrumentation for each composition includes trumpet, saxophone, piano, bass, and drums, with voice on one tune. In addition to the compositions a recording and musical analysis accompany each piece. I presented a lecture recital on June 1, 2015 in Ball State University’s Choral Hall, at which I explained and demonstrated each trumpeter’s influence on my music.